Molecular structure study of a heptakis(2,3,6-tri-O-methyl)-β-cyclodextrin complex of cholesterol - Kučáková, Karolína; Dolenský, Bohumil (Steroids, 2020)
Heptakis(2,3,6-tri-O-methyl)-β-cyclodextrin (2) and cholesterol form a water-soluble complex 3. We performed several NMR studies, particularly 1H, 13C, 2D NOESY and DOSY, at various temperatures on 500 and 950 MHz instruments. We discovered that the complex 3 is unstable above 57 °C in heavy water, while it is kinetically stable enough to be studied by NMR in detail at 1 °C. We demonstrated the formation of a face-to-face 2:1 complex with a binding constant of approximately 2.2 × 106 M-2.
Keywords: Temperature; beta-Cyclodextrins; molekulární struktura; voda; Molecular Structure; Cholesterol; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; NMR; rozpustnost; molekulární modely; Cyclodextrin; Models, Molecular; cholesterol; Structure; beta-cyklodextriny; teplota; Complex; Water; Solubility